2023
DOI: 10.1101/2023.10.31.564947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Story of an infection: viral dynamics and host responses in theCaenorhabditis elegans-Orsay virus pathosystem

Victoria G. Castiglioni,
Maria J. Olmo-Uceda,
Ana Villena-Giménez
et al.

Abstract: SUMMARYOrsay virus (OrV) is the only known natural virus affectingCaenorhabditis elegans, with minimal impact on the worm’s fitness due to its robust innate immune response. This study aimed to understand the interactions betweenC. elegansand OrV by tracking the infection’s progression during larval development. Four distinct stages of infection were identified based on viral load, with a peak in capsid- encoding RNA2 coinciding with the first signs of viral egression. Transcriptomic analysis revealed temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…One limitation here is that we only assessed these parameters at one time point, and the differences in RNAs proportion could also be due to different viral dynamics for both strains. Indeed, we observed different RNA localization patterns for both strains, which have been previously linked to different infection stages of OrV (Castiglioni et al, 2023). A more detailed analysis of the viral dynamics of these strains could shed light into the relevance of the genome formula.…”
Section: Discussionsupporting
confidence: 53%
“…One limitation here is that we only assessed these parameters at one time point, and the differences in RNAs proportion could also be due to different viral dynamics for both strains. Indeed, we observed different RNA localization patterns for both strains, which have been previously linked to different infection stages of OrV (Castiglioni et al, 2023). A more detailed analysis of the viral dynamics of these strains could shed light into the relevance of the genome formula.…”
Section: Discussionsupporting
confidence: 53%
“…The developmental delay does not seem to explain the resistance to infection, as all four C . elegans larval stages are susceptible to infection, as has been shown for the JU1580 [ 45 ] and N2 [ 46 ] strain. Most convincingly we observed that the resistance to viral infections is maintained in mixed bacterial environments that restore the animal development rates.…”
Section: Discussionmentioning
confidence: 69%
“…In the five natural bacterial environments we tested in depth, except for BIGb0102, animals spend more time in their larval stage due to delayed development and the populations thus grow more slowly. The developmental delay does not seem to explain the resistance to infection, as all four C. elegans larval stages are susceptible to infection, as has been shown for the JU1580 [45] and N2 [46] strain. Most convincingly we observed that the resistance to viral infections is maintained in mixed bacterial environments that restore the animal development rates.…”
Section: Discussionmentioning
confidence: 78%
“…Worms were collected with PBS 0.05% Tween and washed 3 times before freezing in liquid N 2 . RNA was extracted using Trizol as previously described (12). RT-qPCRs were performed using Power SYBR Green PCR Master Mix (Applied Biosystems) on an ABI StepOne Plus Real-time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…We first looked into the transcriptional response elicited in infected worms, focusing on genes related to heat stress. For this purpose, we screened the differentially expressed genes upon OrV infection (12) for genes in the following GO-term categories: ( i ) cellular response to unfolded proteins, ( ii ) heat-shock binding proteins and ( iii ) response to heat. The three categories were overrepresented (Fisher’s exact test) among the significant differentially expressed genes (DEGs) upon OrV infection (Fig.…”
Section: Figmentioning
confidence: 99%